Statistical Modelling Technique in Forecasting of Palliative Oncotherapy Load in Hospitals (Nepal Journal of Epidemiology, 2010)
BackgroundAn increase in cancer incidence in developing countries is expected due to the possible decline of mortality from infectious diseases, improved healthcare, population growth and increasing life expectancy. It can therefore be anticipated that the number of cancer patients requiring palliative treatment will also rise in Nepal, creating a discrepancy between the requirement and delivery of health care.  Estimation of trends is very essential for the planning of future requirements in any such programme.Method  This retrospective study analysed the records from the Radiotherapy Department at Manipal Teaching Hospital, Pokhara, Nepal to calculate the number of cancer patients who received palliative treatment with radiotherapy between September 2000 and December 2008. Descriptive statistics was used for the analysis and subsequently, statistical modelling techniques were applied for forecasting of future trends.ResultsOf 1001 cancer cases, 363 patients received radiotherapy with palliative intent during the study period. Excluding the constant term from the equation, the Logarithmic model was the best fitted, with R2 = 0.727, p = 0.002 for the forecasting of cancer patients receiving palliative treatment. Using this model, the number of cancer cases receiving palliative radiotherapy at the hospital in the year 2015 was estimated to be 68. Thus, the number of patients requiring radiotherapy with palliative intent shows a pattern of increasing trend over the coming years.ConclusionThe data analysed in the present study indicates an increasing future trend of patients requiring palliative therapy at the centre. In the future, a discrepancy may arise between the requirement and capacity of care available to these patients. Government and healthcare agencies of Nepal must ready themselves to promote better strategies for adequate provision to the cancer patients receiving palliative treatment in the coming years.Key WordsStatistical Modelling; Palliative Oncotherapy; ForecastingDOI: 10.3126/nje.v1i1.4111Nepal Journal of Epidemiology 2010;1 (1):38-43